Noniatrogenic Neonatal Gastric Perforation: The Role of Interstitial Cells of Cajal. (1st December 2013) - Jactel, Samuel Noah; Abramowsky, Carlos R.; Schniederjan, Matthew; Durham, Megan M.; Ricketts, Richard R.; Clifton, Matthew S.; Langberg, Karl M.; Elawabdeh, Nancy; Pandya, Samir; Talebagha, Sarah; Shehata, Bahig M.
Abstract : Noniatrogenic neonatal gastric perforation is a rare and life-threatening condition whose etiology is often unclear. Interstitial cells of Cajal act as gastrointestinal pacemaker cells and express the proto-oncogene c-Kit. Six new cases were identified at our institution which presented with no mechanical, pharmacologic, or otherwise medical-related intervention prior to rupture. The number of interstitial cells of Cajal in nonnecrotic muscularis propria from five random high-power fields per specimen was compared using immunohistochemical stains for c-Kit. The authors show that a lack of interstitial cells of Cajal in the stomach musculature may be implicated in the development of noniatrogenic gastric perforation ( p = 0.008). Further large-scale studies, including molecular and genetic analysis, may help to better understand this phenomenon.